Peran Pemerintah dalam Pembangunan Daerah Pinggir Kota di Kelurahan Kameloh Baru Kota Palangka Raya - Farida; Jaya, Imanuel; Suprayitno (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2022)
This study discusses the role of government in the development of suburban areas in Palangka Raya City. The aim is to describe how the Government's role in this case is the Kameloh Baru Village Government using the Tjokroamidjojo theory in which the Government is a motivator, facilitator and mobilizer in the implementation of development in the village. This study uses qualitative research methods, the data collection techniques obtained through interviews, observation and documentation. Informants in this study included: Lurah (Head Of Village), Head of Section in Village, Village Employees, Head of neighbourhood, Head of hamlet, and the villager. Information from interviews is also equipped with news documentation and also observations in the field by researchers. The results showed that the Kameloh Baru Village Head as a motivator had not run optimally. Because education and coaching efforts have not been able to increase community participation development in the Kameloh Baru area. The Lurah as a Facilitator, the Kameloh Baru Village Head has not been able to become a facilitator who provides solutions to problems that occur in the area. Lurah as a mobilizer, the coordination between the community and the government is still low. The relationship between the village government and the community is still not well. Obstacles to the Lurah in carrying out his role in development; As a mobilizer, there is still a lack of education provided to the community. So that public awareness is low in the development of the region's development. As a Facilitator, the deliberations between the government and the community have not been optimally carried out, the communication that occurs is still very minimal. As a mobilizer, the Lurah's coordination with the community has not been solidly established. Then the cooperation between the community and the relevant government has not been closely intertwined so that the Lurah's efforts in mobilizing have not been realized optimally.